PHYSIOTHERAPY MANAGEMENT IN COMMON TENDON INJURIES: REVIEW OF REVIEWS (International Journal of Physiotherapy, 2018)
Background: Numerous systematic reviews have been published on tendinopathies that deals with specific therapies on a specific location. Clinical therapists find it difficult to synthesize these results into their practice as evidence is conflicting between the sites of tendinopathy. The objective of this systematic review is to see the effectiveness of physiotherapy interventions (both active- exercise and passive- physical agents) in the management of tendinopathies.Methods: Articles were selected from Web of Science (WoS) by entering keywords in mid-December 2017. Articles published in the English language, between 2000 and 2017 were selected. The author selected 14 reviews from 31 possible reviews for this article and all, but one was indexed in PubMed too. Seven, 1, 3 and 3 were the number of articles that were carried treatment, physiotherapy, exercise and physical agents in their titles. Shoulder, hip or knee, ankle locations were dealt in 6, 4 and four articles respectively.Results: Current evidence-based literature shows that exercise especially eccentric one is the definite physiotherapy treatment option for treating lower limb and some upper limb tendinopathies. However, reviews show that other forms of exercises particularly stabilization as a promising option in upper limb conditions. Physical agents (Ultra Sound [US], Transcutaneous electrical nerve stimulation [TENS] are showing conflicting results hence not recommended at this point. The LASER can be used in Shoulder tendinopathies.Conclusion: The traditional concept of eccentric training in tendinopathies is challenged by recent reviews which show stabilization and other types of exercises also improving pain and function in tendinopathies. Well-designed large RCT trials are required to see the effectiveness of physical agents, different types of exercise training on tendinopathies.